2015
DOI: 10.1111/ejh.12641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of micafungin and voriconazole as empirical antifungal therapies in febrile neutropenic patients with hematological disorders: a randomized controlled trial

Abstract: The clinical efficacy did not differ between micafungin and voriconazole. Micafungin was generally better tolerated than voriconazole when given as an empirical antifungal therapy in patients with persistent fever and neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…4 studies employed the appropriate random sequence generation and allocation concealment [8, 9, 14, 32], while others were unclear due to their failure to state the detailed randomization and allocation method [10, 29, 30]. Authors of 2 RCTs reported that they employed blinded assessors [14, 29] while others were open-label or unclear trials.…”
Section: Resultsmentioning
confidence: 99%
“…4 studies employed the appropriate random sequence generation and allocation concealment [8, 9, 14, 32], while others were unclear due to their failure to state the detailed randomization and allocation method [10, 29, 30]. Authors of 2 RCTs reported that they employed blinded assessors [14, 29] while others were open-label or unclear trials.…”
Section: Resultsmentioning
confidence: 99%
“…The ideal prophylactic antifungal therapy should be safe and well tolerated for long-term use, being effective against a wide spectrum of organisms and available as intravenous and oral formulations with good bioavailability (17). Recent randomized controlled trials (RCTs) (18)(19)(20)(21) and meta-analyses (22)(23)(24) showed a marked reduction of IFIs in patients who used triazoles and echinocandins. The currently available multiple polyenes, echinocandins, and triazoles fulfill some of the requirements for an ideal prophylactic antifungal agent; however, some areas for improvement remain.…”
mentioning
confidence: 99%
“…Figure 2 presents the results of the systematic bias analysis. There was a low risk of bias for most items, except for the presence of performance and detection bias due to the lack of a double-blind design and blind outcome assessment in four studies [ 18 , 22 , 27 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%